2014
DOI: 10.3791/51973
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Custom-designed Galvanotaxis Chambers to Study Directional Migration of Prostate Cells

Abstract: The physiological electric field serves specific biological functions, such as directing cell migration in embryo development, neuronal outgrowth and epithelial wound healing. Applying a direct current electric field to cultured cells in vitro induces directional cell migration, or galvanotaxis. The 2-dimensional galvanotaxis method we demonstrate here is modified with custom-made poly(vinyl chloride) (PVC) chambers, glass surface, platinum electrodes and the use of a motorized stage on which the cells are ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Cells were resuspended in modified Hank’s Balanced solution (mHBSS, Sigma-Aldrich) with 1 μM N-Formyl-Met-Leu-Phe (fMLP, Sigma Aldrich), and then were then plated in a 3D-printed electrotaxis chamber composed of polylactic acid ( Yang et al, 2014 ). Toxicity and changes in pH due to electrode byproducts were minimized by using separate baths for each AgCl electrode and the cell-mHBSS solution, and by connecting the baths using agar bridges in mHBSS (2%, 0.5 cm diameter, created with glass tubing).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were resuspended in modified Hank’s Balanced solution (mHBSS, Sigma-Aldrich) with 1 μM N-Formyl-Met-Leu-Phe (fMLP, Sigma Aldrich), and then were then plated in a 3D-printed electrotaxis chamber composed of polylactic acid ( Yang et al, 2014 ). Toxicity and changes in pH due to electrode byproducts were minimized by using separate baths for each AgCl electrode and the cell-mHBSS solution, and by connecting the baths using agar bridges in mHBSS (2%, 0.5 cm diameter, created with glass tubing).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were resuspended in modified Hank's Balanced solution (mHBSS, Sigma-Aldrich) with 1 µM N-Formyl-Met-Leu-Phe (fMLP, Sigma Aldrich), and then were then plated in a 3D-printed electrotaxis chamber composed of polylactic acid (38). Toxicity and changes in pH due to electrode byproducts were minimized by using separate baths for each AgCl electrode and the cell-mHBSS solution, and by connecting the baths using agar bridges in mHBSS (2%, 0.5 cm diameter, created with glass tubing).…”
Section: Methodsmentioning
confidence: 99%
“…Electrotaxis is a guiding mechanism for the orientation and directional movements of many cell types, including fission yeast cells (12), Caenorhabditis elegans (13)(14)(15)(16), pathogenic bacterium such as Pseudomonas aeruginosa, Escherichia coli, and Dictyostelium (17)(18)(19)(20). It has been reported that some cells migrate toward the cathode [e.g., neural stem cells (21)(22)(23)(24)(25)(26), fibroblasts (27)(28)(29), keratinocytes (30)(31)(32)(33), rat prostate cancer cells (34,35), T lymphocyte (36)(37)(38)(39)(40), lung cancer cells (41)(42)(43)(44)(45), and many epithelial cell types (3,30,(46)(47)(48)(49)(50)(51)], and other cells migrate to the anode [e.g., corneal endothelial cells (52), breast cancer cells (53,54), glioblastoma (55,…”
Section: Introductionmentioning
confidence: 99%